Analisis Tata Ruang Perpustakaan Sekolah - Fitry Aryani; Armiati Armiati (Universitas Negeri Padang, 2021)
This study aims to determine the arrangement of the library space in SMA N 5 Solok Selatan and to know the physical and non-physical conditions of the library space in SMA N 5 Solok Selatan. This research is a descriptive study with qualitative methods which have 2 types of data, namely primary data and secondary data. This research instrument uses a list of interview questions and data collection techniques by conducting observations, interviews, and documentation to support the implementation of this research. Based on the research results, it shows that: the library of SMA N 5 Solok Selatan is in line with the function of the school library in general, where the location of the library can be said to be strategic because it is in the middle of a school environment. However, the area of the library building / space is currently categorized as narrow when compared to the large number of students. Then, for the arrangement of the library space is still classified as not paying attention to psychological, functional and aesthetic aspects. Another thing is also seen from the physical condition of the library which is still said to be inadequate, this can be seen from the less bright lighting and the dark and hot air circulation. Meanwhile, the non-physical condition is still incomplete, seen from the lack of furniture and equipment available in the library.